Material and device properties of highly birefringent nematic glasses and polymer networks for organic electroluminescence - Woon, K.L.; Contoret, A.E.A.; Farrar, S.R.; Liedtke, A.; O'Neill, M.; Vlachos, P.; Aldred, M.P.; Kelly, S.M. (Wiley, 2006)
Light-emitting nematic liquid crystals are promising materials for organic light-emitting devices because their orientational anisotropy allows polarized electroluminescence and improved carrier transport. Two classes of nematics, i.e., room-temperature glasses and crosslinked polymer networks are discussed. The latter class has an additional advantage in that photolithography can be used to pixelate a full-color display. We show that the order parameter and birefringence of a new light-emitting nematic liquid crystal with an extended aromatic core both have values greater than 0.9. The performance of green light-emitting devices incorporating liquid crystals of different conjugation lengths is discussed. Efficacies up to 11.1 cd/A at 1160 cd/m2 at an operating voltage of 7 V were obtained. A spatially graded, color organic light-emitting device obtained by overlapping pixels of blue-, green-, and red-emitting liquid crystals were demonstrated. Some regions of the red pixel were only partially photopolymerized in order to obtain different hues in the overlapping region with green. We also show that the photolithographic process has micron-scale resolution.